Forty questions of importance to the policy and practice of native oyster reef restoration in Europe. Issue 11 (12th November 2020) - zu Ermgassen, Philine S. E.; Bonačić, Kruno; Boudry, Pierre; Bromley, Cass A.; Cameron, Tom C.; Colsoul, Bérenger; Coolen, Joop W. P.; Frankić, Anamarija; Hancock, Boze; van der Have, Tom M.; Holbrook, Zoë; Kamermans, Pauline; et al.
Abstract: Oyster reefs are among the most threatened marine habitats globally. In Europe, oyster reefs have been extirpated from most locations within their historical range. Active restoration of the native oyster ( Ostrea edulis ) in Europe has grown substantially in recent years. In sharing experiences between oyster restoration projects in Europe at the Native Oyster Restoration Alliance conference, NORA2, in Edinburgh in May 2019, it became apparent that a number of similar barriers are experienced. This study identified the top 40 questions, which, if answered, would have the greatest influence on the policy and practice of oyster restoration in Europe. Initially 71 people were consulted across 28 institutions and 11 European countries to generate 194 questions. An established process of one round of pre‐workshop voting followed by a one‐day online workshop and two post‐workshop rounds of voting resulted in the final 40 questions. Questions were broadly grouped into the following 10 themes: baselines, site selection, restoration methods, quantifying benefits, disease management, biosecurity, genetic diversity and population differentiation, policy and management, novel technologies, and current and future threats. We anticipate that this list will provide a starting point for developing collaborative projects across the NORA network, as well as assisting policy makers and funders with identifying key areas that need to be addressed in order to overcome existing barriers to scaling up oyster restoration in Europe.